Penetrating trauma in children on the United States-Mexico border: Hispanic ethnicity is not a risk factor. Issue 7 (July 2018) - Vo, Loc-Uyen T.; Anderson, Clark; Thomas, Samantha; Vernia, Hannah; Howe, Jarett K.; Tyroch, Alan H.; Fitzgerald, Tamara N.
Abstract: Introduction: The United States-Mexico border is perceived as dangerous by the media and current political leaders. Hispanic ethnicity, low socioeconomic status, male gender and adolescent age have previously been identified as risk factors for penetrating trauma (PT). Methods: A retrospective review of PT was performed in a border region. Children 0–17 years old, admitted to the region's only level I trauma center between 2001 and 2016 were included. Standardized morbidity ratio was used to compare observed to expected morbidity. Results: There were 417 PT admissions. 197 (47%) were non-accidental, 34 (8%) suicide attempts and 186 (45%) accidental. There were 12 homicides, 7 suicides and no accidental deaths. The region contains over 280, 000 children, thus yielding a homicide rate of 0.26 per 100, 000. The U.S. pediatric homicide rate was 2.6–4.0 over this period. Adolescents 13–17 years old accounted for 237 (57%) admissions, 152 (78%) of non-accidental admissions and 12 (63%) deaths. Most admissions (N = 321, 77%) and 15 of the deaths (79%) were males. Non-accidental injuries were more frequent in ZIP codes associated with low incomes. Hispanic patients accounted for 173 (88%) of non-accidental trauma. However, 40 (20%) non-accidental injuries occurred in Mexico and 157 (80%) injuries occurred in an 82% Hispanic region. Therefore, the standardized morbidity ratio for Hispanic ethnicity was 1.048 (CL 0.8–1.2, P = 0.6). Conclusion: On the United States-Mexico border, the pediatric homicide rate was less than 1/10 the national average. Male adolescents are at risk for non-accidental PT. In a Hispanic majority population, Hispanic ethnicity was not a risk factor for PT. It is possible that economic disparity, rather than race/ethnicity, is a risk factor for PT.